Validation of Modified Mallampati Test with Addition of Thyromental Distance and Sternomental Distance to Predict Difficult Endotracheal Intubation in Adults Presenting in Surgical Emergency - Muhammad Usman Mohsin, Muhammad Adnan, Muhammad Aatir Fayyaz, Hassan Raza, Muhammad Zaman Habib, Muhammad Kaleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To validate modified mallampati test with addition of thyromental distance and sternomental distance in prediction of difficult endotracheal intubation in adults presenting in surgical emergency. Study Deign: Prospective, single-blinded observational study Place and duration: Department of Anesthesia and intensive care Nishtar Hospital, Multan from August 2021 to January 2022 in one year duration. Methodology: A total of 120 patients were included in the study. Difficult intubation was predicted by measuring modified mallampati test following thyromental distance and sternomental distance. Validation of mallampati test and combining predictors was assessed by measuring sensitivity, specificity, positive & negative predictive value. Contingency table 2x2was designed. Results: The sensitivity and specificity of this procedure was 62.5% and 80.0%, respectively. Validity of combining all parameters to predict the difficult in endotracheal intubation was shown in table IV. The sensitivity and specificity of this procedure was 25.0% and 27.0%, respectively. Practical Implication: Endotracheal intubation is a common pre-operative complication having potential to lead poor post operative results. This study will help the anesthesiologists to overcome the problem of intubation and reduce the incidence of post operative complications in routine practice. Conclusion: Specificity of modified mallampati is too high, validity of combine parameters modified mallampati, sternomental distance and thyromental distance is very high when compared with mallampati test alone. All three parameters MMT, SMD and TMD can be used collectively for assessment of difficult airway in adult patients planned for surgery under general anesthesia. Keywords: Validity, anaesthesia, modified Mallampati test, endotracheal intubation, thyromental distance, sternomental distance